A pre-lithiation coated lithium cobalt oxide positive electrode material and preparation method thereof
Through the prelithiated coating method, the double coating structure of tin and carbon is used to solve the problem of poor electrochemical performance of lithium cobalt oxide cathode material under oxygen atmosphere, achieving high conductivity and cyclic stability, and avoiding lithium cobalt oxide reduction.
Patent Information
- Application Number
- CN202210298894.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-03-25
AI Technical Summary
The prior art is difficult to effectively realize the carbon-coated lithium cobalt oxide positive electrode material under an oxygen atmosphere, resulting in poor electrochemical performance, and traditional methods are prone to reduction of cobalt metal ions.
By using the prelithiated coating method, lithium cobalt oxide is mixed with tin tetrachloride, lithium hydroxide and polymer carbon sources in anhydrous ethanol, and calcined in an oxygen-containing atmosphere to form a double coated structure of tin and carbon. Avoid reduction of lithium cobalt oxide and improve its conductivity.
The excellent conductivity and cyclic properties of lithium cobalt oxide positive electrode material are achieved, which significantly improves its electrochemical properties, avoids the reduction of lithium cobalt oxide, and enhances the stability of the material.
Smart Images

Figure CN114709387B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery positive electrode materials, and in particular relates to a pre-lithiation coated lithium cobalt oxide positive electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion secondary batteries have the characteristics of high energy density, light weight, no pollution to the environment, no memory effect, stable working performance, safety and reliability. Since their advent, they have been widely used and have become the main portable power source at present, and are also the development focus of high-power dynamic batteries.
[0003] In lithium-ion batteries, the positive electrode material is the most important component and the key to determining the performance of lithium-ion batteries. Layered positive electrode materials for lithium-ion batteries are a hot topic in the field. In theory, materials with layered structures and spinel structures can be used as positive electrode materials for lithium-ion batteries. Among them, lithium cobalt oxide used as a positive electrode material for lithium-ion batteries has the following characteristics: 1. Good safety; 2. Average capacity; 3. Average cycle performance. Lithium cobalt oxide has been widely used as a positive electrode material and has been industrialized. The research is relatively mature and has excellent comprehensive performance.
[0004] As people learn more about electrode materials for lithium-ion batteries, they find that their surface structure has a great influence on their electrochemical properties. Carbon coating has become one of the most widely used methods in lithium-ion batteries due to the excellent conductivity, ultra-high chemical and electrochemical stability, unique physical properties and low cost of carbon materials. Carbon coating can effectively improve electrode conductivity, improve the surface chemistry of active materials, and protect electrodes from direct contact with electrolytes, thereby achieving better cycle life. Carbon coating combined with nanotechnology can provide better conductivity and faster lithium ion diffusion, thereby achieving better rate performance. In particular, carbon-coated lithium iron phosphate has promoted the transition of lithium iron phosphate from the laboratory to industrialization. Therefore, research on carbon coating of positive electrode materials is of great significance.
[0005] Because the synthesis conditions of lithium cobalt oxide are in air or oxygen atmosphere, the synthesis temperature is as high as 900°C. Therefore, the traditional method of achieving carbon coating by decomposing organic carbon is difficult to achieve on lithium cobalt oxide: first, carbon coating must be in an inert atmosphere, which conflicts with the need for oxygen atmosphere for lithium cobalt oxide synthesis; second, the temperature for carbon decomposition and graphitization is as high as 700°C-900°C, which can easily reduce cobalt metal ions to simple substances or CoO or Co3O4. Therefore, it is urgent to develop a method for carbon coating of lithium cobalt oxide to prepare positive electrode materials with excellent electrochemical properties. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a pre-lithiation coated lithium cobalt oxide positive electrode material and a preparation method thereof, wherein the positive electrode material prepared by the method has excellent electrochemical properties.
[0007] The above technical objectives of the present invention are achieved through the following technical solutions:
[0008] A method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material comprises the following steps: (1) adding lithium cobalt oxide into anhydrous ethanol and mixing; (2) adding tin tetrachloride and lithium hydroxide into the mixed solution of step (1), and adding a carbon source and mixing; (3) evaporating the mixed solution obtained in step (2); and (4) calcining the material evaporated in step (3) in an oxygen-containing atmosphere, cooling, washing, and drying to obtain the material.
[0009] Preferably, in step (1), the mass ratio of lithium cobalt oxide to anhydrous ethanol is 1:(1-3).
[0010] Preferably, in step (2), the molar ratio of tin tetrachloride, lithium hydroxide and lithium cobaltate is 1:6:(80-100).
[0011] Preferably, the mass of the carbon source added in step (2) is 10-30% of the mass of the lithium cobalt oxide.
[0012] Preferably, the carbon source is at least one of polyacrylic acid, polyethylene oxide, and polypropylene alcohol.
[0013] Preferably, the temperature for evaporation to dryness in step (3) is 75-85°C.
[0014] Preferably, the oxygen-containing atmosphere in step (4) is a mixed gas of nitrogen and oxygen, and the volume ratio of nitrogen to oxygen is 10:(1-3).
[0015] Preferably, the calcination temperature in step (4) is 300-450° C., and the calcination time is 3-6 hours.
[0016] Preferably, in step (4), the washing is performed by using anhydrous ethanol to wash the material after it has been cooled to room temperature.
[0017] Preferably, the drying temperature in step (4) is 80-120° C., and the drying time is 1-3 h.
[0018] Preferably, a method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material comprises the following steps:
[0019] (1) adding lithium cobalt oxide to anhydrous ethanol in a mass ratio of 1:(1-3) and mixing well;
[0020] (2) adding tin tetrachloride and lithium hydroxide to the mixed solution of step (1) according to the molar ratio of tin tetrachloride, lithium hydroxide and the lithium cobalt oxide described in step (1) of 1:6:(80-100), and adding a polymer carbon source of 10-30% by mass of the lithium cobalt oxide to the mixed solution, stirring for 1-2 hours, and uniformly mixing; the polymer carbon source is at least one of polyacrylic acid, polyethylene oxide, and polypropylene alcohol;
[0021] (3) evaporating the mixed solution to dryness at 75-85° C. and recovering ethanol;
[0022] (4) placing the evaporated material in a tube furnace and introducing a mixture of nitrogen and oxygen, calcining at 300-450° C. for 3-6 h, wherein the volume ratio of nitrogen to oxygen in the mixture is 10:(1-3);
[0023] (5) After the calcined material is cooled to room temperature, the calcined material is washed with anhydrous ethanol;
[0024] (6) The washed material is dried at 80-120° C. for 1-3 h to obtain a pre-lithiation coated lithium cobalt oxide positive electrode material.
[0025] A pre-lithiation coated lithium cobalt oxide positive electrode material is prepared by the preparation method as described above.
[0026] The beneficial effects of the present invention are:
[0027] (1) In the preparation method of the pre-lithiation coated lithium cobalt oxide positive electrode material of the present invention, anhydrous ethanol is used as a solvent, lithium cobalt oxide, tin tetrachloride, lithium hydroxide and a polymer carbon source are blended, the ethanol is evaporated and recovered, and the polymer is further calcined to carbonize the polymer, thereby obtaining a carbon-coated lithium cobalt oxide positive electrode material. The carbonization reaction mechanism of the preparation method of the pre-lithiation coated lithium cobalt oxide positive electrode material of the present invention is as follows: first, 6LiOH+SnCl4=4LiCl+Li2Sn(OH)6, and the generated Li2Sn(OH)6 is Li2SnO3·3H2O, Coated on the surface of lithium cobalt oxide, while further supplementing the lithium source, a coating surface blended with a polymer carbon source is formed. The polymer carbon source is very easy to generate hydrogen free radicals during the carbonization process, and the tetravalent tin in lithium stannate (which can be regarded as lithium oxide and tin dioxide) reacts with it to prevent the surface lithium cobalt oxide from being reduced: SnO2+2H·=SnO+H2O, 2SnO+O2=2SnO2, thereby solidifying and stabilizing the carbon chain in the polymer, thereby obtaining a lithium cobalt oxide positive electrode material doubly coated with tin and carbon. The obtained carbon-coated lithium cobalt oxide positive electrode material has excellent conductivity and cycle performance.
[0028] (2) The method for preparing the pre-lithiated coated lithium cobalt oxide positive electrode material of the present invention uses ethanol as the dissolving solvent, which can avoid the dissolution of lithium in the lithium cobalt oxide material.
[0029] (3) In the preparation method of the pre-lithiation coated lithium cobalt oxide positive electrode material of the present invention, tin tetrachloride is reacted with lithium hydroxide to generate lithium stannate and lithium chloride. During calcination, in addition to further pre-lithiation of the lithium cobalt oxide material, the tin in the lithium stannate also acts as a flame retardant to prevent the complete combustion of the polymer carbon source, which is more conducive to its carbonization, thereby forming a carbon-coated lithium cobalt oxide positive electrode material. At the same time, during the calcination process, by controlling the nitrogen-oxygen ratio, on the one hand, it is conducive to the carbonization of the polymer carbon source, and on the other hand, it is further prevented that the polymer carbon source reduces the lithium cobalt oxide. Finally, lithium chloride is easily soluble in ethanol and lithium in the lithium cobalt oxide is prevented from being eluted. The residual lithium chloride is removed by washing with anhydrous ethanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the pre-lithiation coated lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments.
[0032] Embodiment 1:
[0033] A method for preparing a pre-lithiation coated lithium cobalt oxide positive electrode material comprises the following steps:
[0034] (1) adding lithium cobalt oxide to anhydrous ethanol in a mass ratio of 1:3 and mixing well;
[0035] (2) adding tin tetrachloride and lithium hydroxide to the mixed solution of step 1 according to the molar ratio of tin tetrachloride, lithium hydroxide and the lithium cobalt oxide described in step 1 of 1:6:80, and adding a high molecular weight carbon source polyethylene oxide of 30% by mass of lithium cobalt oxide to the mixed solution, stirring for 2 hours, and mixing evenly;
[0036] (3) evaporating the mixed solution to dryness at 85° C. and recovering ethanol;
[0037] (4) placing the evaporated material in a tube furnace and introducing a mixture of nitrogen and oxygen, wherein the volume ratio of nitrogen to oxygen in the mixture is 10:3, and calcining at 450° C. for 3 h;
[0038] (5) After the calcined material is cooled to room temperature, the calcined material is washed with anhydrous ethanol;
[0039] (6) The washed material is dried at 80° C. for 3 h to obtain a pre-lithiation coated lithium cobalt oxide positive electrode material.
[0040] A pre-lithiation coated lithium cobalt oxide positive electrode material is prepared by the above preparation method.
[0041] The SEM image of the prepared pre-lithiation coated lithium cobalt oxide positive electrode material is as follows: Figure 1shown.
[0042] Embodiment 2:
[0043] A method for preparing a pre-lithiation coated lithium cobalt oxide positive electrode material comprises the following steps:
[0044] (1) adding lithium cobalt oxide to anhydrous ethanol in a mass ratio of 1:2 and mixing well;
[0045] (2) adding tin tetrachloride and lithium hydroxide to the mixed solution of step 1 according to the molar ratio of tin tetrachloride, lithium hydroxide and the lithium cobalt oxide described in step 1 to 1:6:90, and adding a high molecular weight carbon source polyacrylic acid in an amount of 20% by mass of the lithium cobalt oxide to the mixed solution, stirring for 1.5 hours to mix evenly;
[0046] (3) evaporating the mixed solution to dryness at 80° C. and recovering ethanol;
[0047] (4) placing the evaporated material in a tube furnace and introducing a mixture of nitrogen and oxygen, calcining at 400° C. for 4 h, wherein the volume ratio of nitrogen to oxygen in the mixture is 10:2;
[0048] (5) After the calcined material is cooled to room temperature, the calcined material is washed with anhydrous ethanol;
[0049] (6) The washed material is dried at 100° C. for 2 h to obtain a pre-lithiation coated lithium cobalt oxide positive electrode material.
[0050] A pre-lithiation coated lithium cobalt oxide positive electrode material is prepared by the above preparation method.
[0051] Embodiment 3:
[0052] A method for preparing a pre-lithiation coated lithium cobalt oxide positive electrode material comprises the following steps:
[0053] (1) adding lithium cobalt oxide to anhydrous ethanol in a mass ratio of 1:1 and mixing well;
[0054] (2) adding tin tetrachloride and lithium hydroxide to the mixed solution of step 1 according to the molar ratio of tin tetrachloride, lithium hydroxide and the lithium cobalt oxide described in step 1 to 1:6:100, and adding a high molecular carbon source polypropylene alcohol of 10% by mass of lithium cobalt oxide to the mixed solution, stirring for 1 hour, and mixing evenly;
[0055] (3) evaporating the mixed solution to dryness at 75° C. and recovering ethanol;
[0056] (4) placing the evaporated material in a tube furnace and introducing a mixture of nitrogen and oxygen, calcining at 300° C. for 6 h, wherein the volume ratio of nitrogen to oxygen in the mixture is 10:1;
[0057] (5) After the calcined material is cooled to room temperature, the calcined material is washed with anhydrous ethanol;
[0058] (6) The washed material is dried at 120° C. for 1 h to obtain a pre-lithiation coated lithium cobalt oxide positive electrode material.
[0059] A pre-lithiation coated lithium cobalt oxide positive electrode material is prepared by the above preparation method.
[0060] Test example:
[0061] The conductivity test was performed on the pre-lithiation coated lithium cobalt oxide positive electrode materials prepared in Examples 1-3 and the lithium cobalt oxide raw materials used in Examples 1-3, respectively. The test results are shown in Table 1.
[0062] Table 1: Conductivity test results
[0063] Conductivity(s / cm) Volume resistivity (Ω·cm) Example 1 <![CDATA[5.63×10 -2 ]]> 83.6 Example 2 <![CDATA[5.16×10 -2 ]]> 80.1 Example 3 <![CDATA[4.82×10 -2 ]]> 76.5 Lithium cobalt oxide raw materials <![CDATA[2.83×10 -3 ]]> 373.1
[0064] As shown in Table 1, the pre-lithiation coated lithium cobalt oxide positive electrode material prepared by the preparation method of the present invention has excellent conductivity, and its conductivity is 4.82×10 -2 s / cm and above, which is much larger than the conductivity of lithium cobalt oxide raw materials, and the volume resistivity is 83.6Ω·cm and below, which is much smaller than the volume resistivity of lithium cobalt oxide raw materials.
[0065] The pre-lithiation coated lithium cobalt oxide positive electrode material prepared in Example 1-3 and the lithium cobalt oxide raw material used in Example 1-3 were used as active materials, acetylene black was used as a conductive agent, and PVDF was used as a binder. The active material, conductive agent, and binder were weighed in a ratio of 92:4:4, and a certain amount of organic solvent NMP was added. After stirring, they were coated on aluminum foil to make a positive electrode sheet. The negative electrode used a metal lithium sheet and a CR2430 button battery was made in a glove box filled with argon. The electrical performance test was carried out in a CT2001A blue electric test system. Test conditions: 3.0-4.48V, current density 1C=180mAh / g, and the test temperature was 25±1°C. The test results are shown in the following table.
[0066] Table 2: Battery performance test results
[0067]
[0068] It can be seen from Table 2 that the pre-lithiation coated lithium cobalt oxide positive electrode material prepared by the preparation method of the present invention has a high discharge capacity and good cycle stability. Its discharge capacity is 216.7 mAh / g or above, which is much larger than the discharge capacity of the lithium cobalt oxide raw material. At the same time, its capacity retention rate after 600 cycles is 85% or above, which is much larger than the capacity retention rate of the lithium cobalt oxide raw material after 600 cycles.
[0069] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a pre-lithiation coated lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: (1) Add lithium cobalt oxide to anhydrous ethanol and mix; (2) adding tin tetrachloride and lithium hydroxide to the mixed solution of step (1), and adding a carbon source to mix; (3) evaporating the mixed solution obtained in step (2) to dryness; (4) calcining the material evaporated to dryness in step (3) in an oxygen-containing atmosphere, cooling, washing and drying to obtain the product; the oxygen-containing atmosphere in step (4) is a mixed gas of nitrogen and oxygen, and the volume ratio of nitrogen to oxygen is 10:(1-3); the calcination temperature in step (4) is 300-450° C., and the calcination time is 3-6 hours; the washing in step (4) is washing the material cooled to room temperature with anhydrous ethanol; the carbon source is at least one of polyacrylic acid, polyethylene oxide and polypropylene alcohol.
2. The method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In step (1), the mass ratio of lithium cobalt oxide to anhydrous ethanol is 1:(1-3).
3. The method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In step (2), the molar ratio of tin tetrachloride, lithium hydroxide and lithium cobalt oxide is 1:6:(80-100).
4. The method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The mass of the carbon source added in step (2) is 10-30% of the mass of the lithium cobalt oxide.
5. The method for preparing a pre-lithiated coated lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The temperature for evaporation to dryness in step (3) is 75-85°C.
6. A pre-lithiation coated lithium cobalt oxide positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
High-voltage lithium ion battery and cathode material thereof
CN102623694A
Preparation method for lithium ion battery anode composite material
CN103700834A
Lithium cobalt oxide composite material coated with lithium orthosilicate and carbon, preparation method and application
CN113299915A